Implementation of Online Dispute Resolution Sharia Arbitration in the New Normal Era (Basyarnas-Indonesia) - Yuli Hartati S, Sawitri; Rusdi Daud, Muhammad; ., Mardani; Azizah, Aprida (KnE Social Sciences, 2024)
Changes in behavior to continue carrying out normal activities or continuing habits that were previously carried out during the implementation of regional quarantine or large-scale social restrictions (PSBB) are the post-Covid 19 new normal era. This also affects behavior in the world of justice, especially trials that are carried out simply and quickly. This research will also discuss the use of online dispute resolution (ODR) that can be applied in Sharia economic dispute cases at Basyarnas, and understanding in terms of examinations based on electronic evidence other than written evidence. Also for the sake of caution that must be examined regarding physical evidence in court so that this evidence gains strength and validity according to the law as an update in court administration to overcome obstacles in the process of conducting an effective and efficient trial. The nature of this research is an analytical perspective and modernly the Supreme Court with Permanya Number 1 of 2019 regarding trials in court electronically implemented for the sake of legal certainty. So dispute resolution is non-litigation in the muamalah field. Though Sharia Arbitration, can be done by ODR. Keywords: implementation, Sharia arbitration, ODR